Surface-Emitting Metal Nanocavity Lasers. (16th October 2011) - Hill, Martin T.; Marell, Milan J. H.
Abstract : There has been considerable interest in metallic nanolasers recently and some forms of these devices constructed from semiconductor pillars can be considered as surface-emitting lasers. We compare two different realized versions of these nanopillar devices, one with a trapped cutoff mode in the pillar, another with a mode that propagates along the pillar. For the cutoff mode devices we introduce a method to improve the output beam characteristics and look at some of the challenges in improving such devices.